Hubungan Triangular of love dan Relationship Satisfaction pada Pasangan Emerging Adulthood yang Sedang Menjalin Hubungan Romantis - Dewanto, Hajar; Sahrani, Riana; Budiarto, Yohanes (Universitas Muhammadiyah Metro, 2025)
This study examines the influence of intimacy, passion, and commitment within Sternberg’s Triangular Theory of Love on relationship satisfaction among individuals in emerging adulthood. This developmental stage is characterized by identity exploration and the transition toward long-term commitments, during which many individuals face challenges in building satisfying relationships. A quantitative, non-experimental design with dyadic analysis was employed. Participants consisted of 260 individuals (130 couples), aged 18–29 years, who were currently in romantic relationships. Data were collected through an online survey using the Triangular Love Scale (TLS) and the Relationship Assessment Scale (RAS). Analysis was conducted using the Actor–Partner Interdependence Model with Multilevel Modeling (APIM-MM) in SPSS to test both actor effects and partner effects on relationship satisfaction. Findings indicate that all three love components were significantly associated with relationship satisfaction. However, the APIM-MM analysis revealed that only actor effects had a significant impact, whereas partner effects were not statistically meaningful. These results suggest that relationship satisfaction is more strongly shaped by individuals’ own perceptions of their relationships rather than by their partners’ actions. This study provides new insights into the dynamics of romantic relationships in emerging adulthood and offers implications for future research and relational psychology practices.